Pandangan Kritis terhadap Pendekatan Feminis - Ahmad Adnan (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2016)
Indeed, the mission of man on earth is not just worship. But there are other missions into the principles and values ??of the mission on this earth. It begins with a noble task as a manager and developer of this earth that are beneficial to humans and as a means of worship. This is called the prosperity of the earth. Leadership is: the ability to manage, organize, memenaj, regulate, administer, build, guide, and provide tranquility, peace, and security and guarantees to institutions that are under the authority consisting of a group of people, territorial and all of its assets. He is a gift and a burden of responsibility from God for His servants, especially a human, he is a caliph, manager, and leader as verses in discussion-discussion beforehand. Leadership is a responsibility that must be carried out jointly between men and women.